Initial Capital Constraints Hinder Entrepreneurial Venture Performance: An empirical analysis - Mirjam van Praag (Center for Economic Studies and ifo Institute (CESifo), 2003)
A novel method is applied to evaluate the effect of capital constraints on entrepreneurial performance on a panel of 1,000 Dutch entrepreneurs. We find that initial capital constraints hinder entrepreneurs in their performance, even when we control for various human capital and other factors that might affect both performance and credit scoring outcomes. We use a direct individual indicator variable for initial capital constraints. Previous research with the same objective used indirect indicators of wealth, inheritances or windfall gains, where it remains unknown whether the entrepreneur indeed suffered from capital constraints. This drawback is not attached to our (neither perfect) approach so that policy implications will become more evident.
Keywords: 330; entrepreneurship; small business founders; success; venture performance; wealth/capital/borrowing constraint